Qīmat al-ʿAdl wa-Atharuhā fī Bināʾ al-Insān min Khilāl Sūrat al-Nisāʾ:Dirāsah fī al-Tafsīr al-Mawḍūʿī - Dia, Yousouf Ibrahim; Adim, Fauzan (Al-Zahra : Journal for Islamic and Arabic Studies, 2025)
This research stems from a firm will and desire to explore the Qur’anic guidance on human development by highlighting the value of justice in Surah An-Nisa. A comprehensive and brief look at the guidance, knowledge, and objectives found in Surah An-Nisa clearly reveals the significance of justice, as the surah explains and demonstrates its fundamental, general, and detailed principles—whether ethical, human, political, social, legal, judicial, or international, on individual, family, or societal levels. Just as the essence of religion is inseparable from monotheism (tawhid), it also cannot thrive without the spirit of justice. The Qur'an establishes everything on the foundation of justice and fairness, and revolves around these two principles. This research is a qualitative study based on classical and contemporary works of Tafsir and Qur’anic sciences, as well as linguistic references particularly those related to the concept of justice in the Qur’an. It is further supported by secondary sources, including scholarly articles, books, and academic publications. Using the descriptive-analytical method, the study concludes that justice plays a significant role in the development and advancement of both individuals and societies. Surah An-Nisa offers clear guidance on this through its various themes and issues.